ODPOWIEDZIALNOŚĆ ODSZKODOWAWCZA Z TYTUŁU BEZPRAWIA NORMATYWNEGO - Safjan, Marek (Wydział Prawa i Administracji UAM, 2005)
The non-conformity to the Constitution (determined by a superior act of law) is not equivalent to the occurrence of illegality as a prerequisite of ex delicto liability. Normative illegality may specifically concern a precisely defined area for the binding force of a given regulation and not the whole period of the binding force of the normative act (this is clearly acknowledged by the so-called secondary non-constitutionality of the regulation resulting from the new Polish Constitution entering into force). The so-called legislative failure to act (the non-issuing of a normative act) is a specific form of normative illegality (art. 417 § 4). The interpretation of the prerequisites of such liability must respect one of the basic principles of a democratic state ruled by law i.e. the principle of separation and balance between the legislative, executive and judicial powers (Art. 10 Constitution). The interpretation of the term “legislative failure to act” may under no circumstance lead to independent stipulation, by the court examining a claim for damages, of the contents of the not adopted legal regulations. The broad view of ex delicto liability prerequisites, when referring to activities connected with the realisation of the public powers empire, should incline towards the far reaching consideration when interpreting and applying new mechanisms of liability. For it is very easy to cross the boundary in this respect, which may lead not only to overburdening public finances with unpredictable damages but even to the infringement of the principle of balance and division of powers within the state. Therefore, a lot will depend on rational and considerate judicial practice in this area. Additionally. the strong aspiration to maximize claimant’s protection must not lead to a certain threshold of rationalism being exceeded, since in a further perspective this would cause negative consequences to the claimants themselves and the whole society.
LIABILITY FOR DAMAGES DUE TO NORMATIVE LAWLESSNESS